Free trade and protection of the environment: Is the GATT in need of reform? - Margareta E. Kulessa (Intereconomics, 1992)
The GATT negotiations under the Uruguay Round have almost run their course. However, consultations are certain to continue, as critics regard the GATT rules on environmental protection as inadequate. What aspects need to be reformed, and how might the initial reform measures look?
Keywords: 330; Environmental Policy